LITERATURE REVIEW: DETERMINAN PEMANFAATAN PELAYANAN KESEHATAN PRIMER DI INDONESIA - Sensy Karnia; Hasyim Hasyim; Ainul Hidayah (Bajang Institute, 2026)
The utilization of primary health care is an important aspect in improving public health status in Indonesia because primary care serves as the first point of contact for the community in obtaining promotive, preventive, curative, rehabilitative, and initial referral services. Primary health care services, such as community health centers, first-level health facilities, primary clinics, integrated health posts, and community-based health service networks, play a strategic role in bringing health services closer to all levels of society. This study aims to identify and analyze the determinants of primary health care utilization in Indonesia based on a review of various scientific articles. The method used in this study is a literature review with a qualitative descriptive approach. The articles analyzed were obtained from various national and international scientific sources focusing on primary health care utilization, community health centers, first-level health facilities, the National Health Insurance program, service accessibility, and socioeconomic factors. The selected articles were screened based on topic relevance, information recency, full-text availability, and the relevance of research findings to the determinants of primary health care utilization in Indonesia. The findings from 20 articles in the synthesis table show that the utilization of primary health care in Indonesia is influenced by several interrelated factors. Individual factors include knowledge, attitudes, perceptions of health conditions, perceptions of service benefits, history of illness, and public awareness of the need to seek health care. Socioeconomic factors such as education, occupation, income, and ability to pay also influence people’s decisions to use primary health care services. In addition, membership in the National Health Insurance program is an important factor because it can reduce financial barriers to accessing health services. Accessibility, including distance from residence, availability of transportation, geographical conditions, and affordability of health facilities, is also an influential determinant, particularly for people living in remote areas. Family support, trust in health workers, staff attitudes, waiting time, availability of medicines, and service quality also determine people’s willingness to reuse primary health care services. The conclusion of this literature review shows that the utilization of primary health care in Indonesia is not only determined by the availability of health facilities, but also by individual, socioeconomic, financing, accessibility, social support, and service quality factors. Therefore, efforts to increase primary health care utilization should be carried out through community health education, strengthening the role of the National Health Insurance program, improving equitable access, enhancing service quality, strengthening communication among health workers, and optimizing primary care transformation so that health services become more accessible, high-quality, and sustainable.